Cosmopolitan no more: Phylogenetics and reproductive mode reveal a global species complex in a marine mollusk (Teredinidae) - Nancy C. Treneman; Kelli L. DeLeon; J. Reuben Shipway; Luísa M. S. Borges; Kenneth A. Hayes (PLoS ONE, 2026)
Quantifying biodiversity is challenging when morphology is conserved in taxa with extensive geographic distributions generated in part by human activities. Shipworms, xylophagous wood-boring clams, have been dispersed throughout the world’s oceans by wooden vessels, aquaculture equipment, and in ballast water. Consequently, many species are considered cosmopolitan, with their geographic origin obscured by their extensive distribution. Several cryptic species pairs possessing different reproductive modes are known in the Teredinidae. However, the genetic, ecological, and geographic relationships within these pairs remain unexplored. Members of the Lyrodus pedicellatus complex, both long- and short-term brooders, are found on coastlines of five continents. Phylogenetic, anatomical, ecological, and geographic data were collected on shipworms extracted from test panels, fixed submerged natural wood and driftwood, from multiple locations, primarily in the Hawaiian Archipelago, a center of wooden vessel traffic since the 1400s. Phylogenetic analysis, using multiple loci of L. pedicellatus from Hawaiʻi, Europe, the Mediterranean, Japan, Florida (USA), and California (USA), revealed seven genetically distinct cryptic species comprised of short- and long-term brooders. Reproductive mode was determined to be an inherited trait within the species in this study. Herein we discuss these findings and describe a new member of this complex, Lyrodus reginae sp. nov., from Hawaiʻi. Historically, L. pedicellatus was considered a cosmopolitan species. Our integrative approach reveals a more complicated story, indicating the evolution of multiple cryptic species with different reproductive strategies.